MEWUJUDKAN PELAYANAN PUBLIK YANG PRIMA PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN TABANAN - SURADIGAMA, I WAYAN; ANTARA, I WAYAN; DHARMA, IDA BAGUS WIRYA (Universitas Mahasaraswati K. Mataram, 2023)
Public service is a manifestation of the government's attitude to the community that is prime or primary, to succeed in excellent public service it is also necessary to cooperate with the community, but often in the field, people face obstacles that lack information about the mechanisms or procedures requested by public agencies. such as population management in the civil registry. With the existence of regulations issued by the Tabanan Regency Government, it reflects the government's attitude that prioritizes the community and the government's concentration in serving the interests of the community quickly, so that in managing public services, of course, the human resources in these agencies are always being improved to suppress systems that complicate the community in general, as well as by providing socialization to the community in order to increase public knowledge related to the mechanism for using the system in each intended institution